2022
DOI: 10.3390/ijerph19158940
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Screen Time: Exploring the Associations between Types of Smartphone Use Content and Adolescents’ Social Relationships

Abstract: The past two decades have witnessed controversy over whether the use of digital technology has damaged or enhanced adolescents’ social relationships, which influences their development. In this study, we addressed this debate by specifying the effect of different types of smartphone use content on social relationships, rather than simply relying on screen time spent on digital media. To avoid selective analysis and report of different variables, we used specification curve analysis (SCA) in a large dataset (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, increasing researchers argued that researchers should not only focus on screen time when exploring the health impact of the use of electronic devices for adolescents ( 53 , 54 ). Huang et al explored the associations of smartphone use with adolescents' social relationships in a large dataset, and found that their association relied on the various types of content during smartphone use ( 55 ). In this study, we also focused on the different dimensions of smartphone use to determine the association with BP.…”
Section: Discussionmentioning
confidence: 99%
“…However, increasing researchers argued that researchers should not only focus on screen time when exploring the health impact of the use of electronic devices for adolescents ( 53 , 54 ). Huang et al explored the associations of smartphone use with adolescents' social relationships in a large dataset, and found that their association relied on the various types of content during smartphone use ( 55 ). In this study, we also focused on the different dimensions of smartphone use to determine the association with BP.…”
Section: Discussionmentioning
confidence: 99%
“…Technologies such as smartphones and AI provide various platforms for people to satisfy their entertainment and information-seeking motivations, such as searching for information, listening to music, and playing games. 14,55,70,71 When faced with emotional problems, adolescents tend to motivate themselves to entertain or relax, offsetting negative emotions by using smartphones or social media. 72 However, using technology for entertainment (eg, playing games) carries the risk of becoming addicted to technology use.…”
Section: Ai Entertainment Motivation and Ai Instrumental Motivationmentioning
confidence: 99%
“…As companions literally from early childhood [6,7] to old age [8], smartphones and tablets with the power of supercomputers from the past are not only used as a means of communication in combination with a camera and a range of applications, but also provide access to a wealth of information and resources, making them, at least potentially, a valuable educational tool that combines formal and informal experiences [9]. While the ubiquity of these devices in pockets is becoming a fact of everyday life, their place and role in formal education is controversial, to say the least [10]. While some see them as a valuable educational tool with great potential, others see them more as a distraction from the learning process [11].…”
Section: Introductionmentioning
confidence: 99%